The Impact Of Digital Vision And Cloud Accounting Adoption On MSME Sustainability - Purwantini, Anissa Hakim; Farida, Farida; Maharani, Betari; Dewi, Veni Soraya; Hidayah, Nur (Badan Penerbit Universitas Muria Kudus, 2025)
AbstractThe adoption of technology by Micro, Small, and Medium Enterprises (MSMEs) is crucial for their sustainability. This research investigates the role of digital vision in driving the adoption of cloud accounting among food and beverage MSMEs in Central Java and Yogyakarta. The study further examines the contribution of cloud accounting to enhancing the economic, social, and environmental sustainability of these enterprises. Results from a sample of 167 MSMEs, analyzed using SEM-PLS, indicate a positive relationship between digital vision and cloud accounting adoption. Moreover, cloud accounting adoption positively impacts economic, social, and environmental sustainability.Keyword : MSMEs, digital vision, cloud accounting, sustainability, social, environmental